토픽모델링 기법을 활용한 녹색성장 정책 변화 분석 - 유재호(Yoo, Jae-Ho); 김하나(Kim, Hana); 전의찬(Jeon, Eui-Chan) (한국기후변화학회지, 2021)
In 2008, the Korean president proposed a ‘low carbon, green growth’ sustainable development strategy aimed at preserving the environment and economic growth. It was established as a comprehensive national vision that included energy, environmental issues, jobs, and the greening of the land. This study sought to systematically analyze the Five-Year Plan for Green Growth, which is being implemented in Korea as part of the National Green Growth Strategy, and to extract main topics and keywords related to the green growth strategy over time. This study presented the main topics and keywords of the first to third Five-Year Plan of Green Growth by conducting topic modeling analysis and centrality analysis using NetMiner ver. 4.4.3.d as an analytical tool. Centrality analysis revealed that the first plan had high centrality among keywords associated with green Official Development Assistance (ODA) and education. The second plan placed importance on keywords related to the development and diffusion of green technology. In the third plan, keywords extracted with high centrality were related to low-carbon energy transition. In topic modeling analysis, the main topics of the first plan were Green transportation, Renewable energy promotion, Low carbon product certification, Mitigation and evaluation, and Human resources development. The second plan mainly included Green technology development, Low carbon product certification, Energy demand management, Climate extremes response, and Green ODA. The main topics identified for the third plan were Green transportation, Adaptation, Green ODA, Particulate matter reduction, and Energy transition. “Green traffic” was also commonly mentioned in the first and third plans. However, “bicycle”, one of the major keywords in the first plan, was replaced by “hydrogen and electric vehicles” in the third plan. This suggested that current issues were well reflected in each plan. This study identified the main topics for each planning period, as well as differences and commonalities. This study established how the importance of topics related to mitigation and adaptation have changed by analyzing the Five-Year Plan for Green Growth. KCI Citation Count: 2